Market power in the European dairy industry - Lukas Cechura; Zdenka Žáková Kroupová; Heinrich Hockmann (Agris on-line Papers in Economics and Informatics, 2015)
The paper presents an analysis of market power in the output milk-processing market. In particular, the paper identifies market failures in the output milk-processing market in 24 EU member states. The analysis is based on a mark-up model and the application of stochastic frontier methodology. The results show that market failures are pronounced on the EU output milk-processing market. However, the abuse of oligopoly market power is not large on average, despite the fact that we can find significant differences among the countries. The mark-up distribution is skewed toward lower values. That is, the majority of companies are characterized by only a small or almost no degree of market power; however, there are companies (about 10 %) with considerably high oligopoly market power. – – Článek je zaměřen na analýzu tržní síly na trhu mléčných výrobků. Konkrétně článek identifikuje tržní sílu zpracovatelského trhu mléka ve 24 zemích Evropské unie. Analýza tržní síly je založena na tzv. mark-up modelu a aplikaci přístupu stochastické hraniční funkce. Výsledky prokazují tržní selhání na zpracovatelském trhu mléka v Evropské unii. Zmíněné zneužití oligopolní tržní síly není v průměru velké. Mezi analyzovanými zeměmi však existují významné rozdíly. Rozdělení tržní síly je sešikmené směrem k nižším hodnotám, což znamená, že většina společností disponuje nízkou nebo téměř žádnou tržní silou. Na druhou stranu zde však existují i společnosti (okolo 10 %) se značně vysokou tržní silou.
Keywords: 330; milk; market power; oligopoly; SFA; European Union; mléko; tržní síla; oligopol; Evropská unie